An observational study of cytopathological analysis of ascitic fluid or peritoneal washings cytology in ovarian neoplasms: correlation with histopathological parameters - Jaswani, Priya; Gupta, Sonal (International Journal of Research in Medical Sciences, 2018)
Background: Analysis of ascitic fluid and peritoneal washing cytology serves as a useful predictor of ovarian surface involvement and peritoneal metastasis even in the absence of clinical omental spread. The aim of the current study is to correlate peritoneal cytology with various histologic features of ovarian cancers. Methods: It is a retrospective study. A total of 30 cases of ovarian neoplasms were included in the study. Results of peritoneal cytology were correlated with various histologic features of ovarian tumors including histologic type, grade, tumor size, capsular invasion, and omental metastasis, using chi-square test. A p value of <0.05 was considered as statistically significant. Results: Out of the 30 cases of ovarian tumors involved in the study, twenty-five cases were surface epithelial tumors, two sex-cord stromal tumors, one germ cell tumor, one primary ovarian lymphoma and one metastatic carcinoma. Capsular invasion was seen in 56.3 % of the cases, and omental metastasis in 46.6 % of the cases. A significant positive correlation was seen between positive peritoneal cytology and capsular invasion and omental metastasis with a p value of <0.001. Conclusions: Peritoneal fluid cytology is an indicator of peritoneal metastasis. Positive cytology also correlates with capsular invasion and histologic type in ovarian tumors. Therefore, it should always be used as an adjunctive tool in the surgical management of ovarian tumors.